Verbal mismatch in Right-Node Raising. Issue 1 (18th October 2019) - Shiraïshi, Aoi; Abeillé, Anne; Hemforth, Barbara; Miller, Philip
Abstract : Right-Node Raising (RNR, Ross 1967; Chaves 2014 ) has been claimed to require phonological identity between the missing material and the shared element. Our corpus investigations provide examples of RNR with verb form mismatch with and without syncretism in English and French. Two acceptability experiments show that lack of phonological identity does not affect the acceptability of RNR. We argue further that RNR without phonological identity cannot be taken to be a case of cataphoric VP-ellipsis in French and that it should not be analyzed as such in English. As regards the status of RNR with verb form mismatch, two positions are available: either it is considered to be grammatical, in which case the phonological resolution principle of Pullum & Zwicky (1986 ) does not hold, or it is considered to be ungrammatical but repaired (or "recycled", Arregui et al. 2006 ; Frazier 2013 ). The high acceptability of cases with mismatch compared with ungrammatical controls casts doubt on the applicability of the recycling hypothesis in such cases. In order to account for the broader range of data established by our corpus and experimental results, we propose a new analysis of RNR based on lexeme identity rather than form identity.